New records of Bodotriidae (Crustacea: Cumacea) from Puerto Rico with descriptions of three new species - Petrescu, Iorgu; Chatterjee, Tapas; Schizas, Nikolaos V. (Zootaxa, 2014)
In a continuing effort to describe the cumacean fauna of Puerto Rico we describe three new species of Bodotriidae, a family that has never been reported from Puerto Rico before. While finding and describing new microcrustacean species may not be an impossible task, if there is available taxonomic expertise, the currently described species were found in large numbers within a short distance from the Marine Laboratories of the University of Puerto Rico where the local reefs have been studied for over half a century, highlighting the large gaps that exist in our estimates of Caribbean marine diversity. The three new species, Cyclaspis gurui sp. nov., Cyclaspis mariae sp. nov. and Vaunthompsonia budaii sp. nov. are reported from a fringing reef off La Parguera, southwest coast of Puerto Rico and Vaunthompsonia cristata Bate, 1858 represents a new record for Puerto Rico from the mesophotic reefs.